Neoliberalism and postmodernism: The sacylla and charybdis for critical pedagogy and what can be done about it - Letizia, Angelo (Journal of Interdisciplinary Studies in Education, 2015)
The rise of neoliberalismduring the late 1970s in the West however fundamentally questioned the role ofhigher education institutions in the process of public good formation. Neoliberals and postmodernistgenerally chafe at what they consider improbable utopianism albeit for differentreasons (Allan, 2011). Yet, there are many of us who hold to the ideals of criticalpedagogy and believe that justice can be achieved through education. Thepurpose of this paper is to demonstrate ways in which higher educationinstitutions and critical theorists can create knowledge which promotes the publicgood, in light of neoliberalism and the postmodern critique. Ultimately, I call forthe creation of a new academic discipline, higher education and the public good.